First contribution to the study of Cryptosphaeria from Argentina - Romero, Andrea Irene (2003)
A new species of Cryptosphaeria, from Tierra del Fuego, Argentina, C. sulcata, is described. The representation of this genus in Argentina is low; only C. lignyota and the present species are known. Cryptosphaeria populicola, described by Spegazzini, is a later synonym of Eutypella scoparia. Cryptosphaerina heterospora and C. cumingii, proposed by Spegazzini, are excluded from the Diatrypaceae. Observations of asci with fluorescence microscopy are presented.